2010
DOI: 10.4049/jimmunol.0903188
|View full text |Cite|
|
Sign up to set email alerts
|

HLA-B35 Upregulates Endothelin-1 and Downregulates Endothelial Nitric Oxide Synthase via Endoplasmic Reticulum Stress Response in Endothelial Cells

Abstract: The presence of the HLA-B35 allele has emerged as an important risk factor for the development of isolated pulmonary hypertension in patients with scleroderma, however the mechanisms underlying this association have not been fully elucidated. The goal of our study was to determine the molecular mechanisms that mediate the biological effects of HLA-B35 in endothelial cells (ECs). Our data demonstrate that HLA-B35 expression at physiological levels via adenoviral vector resulted in significantly increased endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
3
39
0
Order By: Relevance
“…It is well documented that inhibition of ER stress by 4-phenylbutyric acid, an ER stress inhibitor, is able to protect cardiac and renal fibrosis in animal models [7,8,9]. With respect to inflammatory responses, it has been reported that ER stress is able to elicit inflammatory responses through activation of NF-κB and the MAPK JNK [10], induction of cytokines such as IFN-β, IL-23, endothelin-1 [11,12,13], activation of the NLRP3 inflammasome [14] and release of TGF-β and expression of collagen I [15]. Thus, prevention and/or reversal of ER stress may serve as one of the possible therapeutic approaches to organ fibrosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that inhibition of ER stress by 4-phenylbutyric acid, an ER stress inhibitor, is able to protect cardiac and renal fibrosis in animal models [7,8,9]. With respect to inflammatory responses, it has been reported that ER stress is able to elicit inflammatory responses through activation of NF-κB and the MAPK JNK [10], induction of cytokines such as IFN-β, IL-23, endothelin-1 [11,12,13], activation of the NLRP3 inflammasome [14] and release of TGF-β and expression of collagen I [15]. Thus, prevention and/or reversal of ER stress may serve as one of the possible therapeutic approaches to organ fibrosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…23-26 The negative effect of ER stress induction on eNOS expression has been recently described in endothelial cells in a model of isolated pulmonary hypertension, and in muscle from CHOP−/− mice. 27,28 Because endothelial nitric oxide synthase (eNOS) plays an important role in maintaining blood pressure and vascular function, our aim is to determine the cellular mechanisms that link ER stress to oxidative stress and how it affects eNOS expression and activity in vascular endothelial cell.…”
Section: Introductionmentioning
confidence: 99%
“…It has been controversial whether eNOS is one of inducing factors for ER stress in endothelial cells. In the systemic cardiovascular system, ER stress results in endothelial dysfunction characterized by reduced eNOS activity and NO bioavailability (Reiter et al, 2000;Lenna et al, 2010;Loinard et al, 2012;Galán et al, 2014). Unlike the systemic circulatory system, NOS expression/activity plays an important role in BBB disruption in the brain vascular system (Mohammadi et al, 2012;Ding et al, 2014;Jiang et al, 2014) Indeed, NO is critical for dysfunction of vascular endothelial cells via ER stress, which facilitates endothelial dysfunction in the brain capillary (Kito et al, 2011;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%